(untitled) - Policar, Clotilde; Rampon, Christine; Balfourier, Alice; Volovitch, Michel; Vriz, Sophie; Bertrand, Hélène Charlotte; Delsuc, Nicolas (Comptes Rendus. Chimie, 2025)
Metal complexes are increasingly used as metallo-probes or metallo-drugs. Their characterization in cellular or biological environments poses specific challenges related to possible decoordination, metal exchange, fixation of additional ligands, or precipitation. These phenomena can hardly be foreseen and it is important to integrate the design of these complexes with their study in cells, from characterization in cells (quantification, speciation, integrity of the complex in cells, location) to bioactivity. Redox homeostasis and oxidative stress are strongly associated with biochemistry of metal ions. Metalloenzymes protecting against oxidative stress have evolved such as catalase or superoxide dismutase. Bioactive antioxidant metal complexes can be designed as catalysts bioinspired from these natural antioxidant enzymes protecting the cell against oxidative stress. To characterize their activity, it is important to develop dedicated cellular models to evaluate their ability to restore normal cell life from a situation compromised by oxidative stress. This article describes cellular models and assays that have been developed in that context as well as approaches to interrogate the complexes’ nature in cells.